Impact of Pea Protein Isolate Enrichment on the Nutritional, Functional, and Glycemic Properties of Tarhana - Kadam, Aayushi; Ozkan, Kubra; Du, Peifan; Koksel, Hamit; Sagdic, Osman; Koksel, Filiz (SPRINGER, 2025)
Tarhana, a traditional fermented food made from cereal flours, yogurt, vegetables, and spices, is recognized for its rich nutritional value and prolonged shelf life. This study investigated the effect of pea protein isolate (PPI) enrichment on select compositional, physical, techno-functional and nutritional properties of tarhana. Six different formulations were prepared by blending PPI and wheat flour (WF) in varying PPI: WF ratios from 0:100 (control) to 100:0. The protein content of the tarhana samples increased proportionally with the PPI concentration, reaching 76.6% in the PPI: WF of 100:0 PPI tarhana compared to 25.1% in the control tarhana. The total phenolic content (TPC) varied, ranging from 534.1 to 702.9 mg GAE/100 g dry basis (db), with higher values observed in PPI enriched tarhana samples. PPI enrichment significantly (p < 0.05) enhanced the antioxidant capacity, measured by ABTS, DPPH, and FRAP assays. PPI-enriched tarhana powders showed improved levels of key polyphenols, including gallic acid, quercetin and ferulic acid. Pasting profile of the tarhana samples showed a decrease in peak viscosity with increasing PPI, indicating the decrease in starch concentration. In-vitro protein digestibility of tarhana samples improved with PPI incorporation, showing values exceeding 84% for all PPI enriched formulations. The glycemic index (GI) of the tarhana samples decreased with increased PPI levels. Tarhana soups made from PPI: WF of 80:20 and 100:0 showed GI values 50.5 and 42.6, respectively, enabling them to be classified as low-GI foods. This research highlighted the potential of PPI to enhance the nutritional and functional properties of traditional tarhana.
Keywords: Fermentation; Phenolics; Antioxidant capacity; Protein digestibility; Functional foods; IN-VITRO DIGESTIBILITY; ANTIOXIDANT ACTIVITY; PASTING PROPERTIES; INDEX; FLOURS; LENTIL; Plant Sciences; Chemistry; Food Science & Technology; Nutrition & Dietetics